Airport economic regulation and capital investment: lessons from the United Kingdom experience - Pagliari, Romano (International Center for Competitiveness Studies in the Aviation Industry, 2008)
ICCSAI´s annual Fact Book is a bianually updated and synthetic reference document on competition in the air transport industry of Europe. Special attention is given to the Italian context, although these data are discussed from an international perspective. This work is addressed to all players in the air transport industry. It presents detailed information on demand, supply, industry structure, and regulation policies. Moreover, we draw broad conclusions from these data and identify key questions for future research. We endeavor to approach topics debated in the literature from the standpoint of those who work in the air transport industry as operators or policy makers.